Scrambling of bands in gel electrophoresis of DNA. - Lalande, M (1988)
Under certain conditions of agarose gel electrophoresis, larger DNA molecules migrate faster than smaller ones. This anomalous mobility of DNA, which can lead to serious errors in the measurement of DNA fragment lengths, is related to near-zero velocity conformations which can trap DNA chains during electrophoresis. Intermittent electric fields can be used to alter the chain conformations so as to restore the monotonic mobility-size relationship which is necessary for a correct interpretation of the gel. These data are in agreement with the results of a computer simulation based on a theoretical model of electrophoresis.